1995
DOI: 10.1177/00220345950740040501
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of IL-1β, TNF-α, IL-6, and IL-8 in Human Monocytes in Response to Lipopolysaccharides from Different Microbes

Abstract: Macrophages respond to bacterial lipopolysaccharides (LPS) and activate several host defense functions through production of mediators. However, it is not clear whether the degree of macrophage responsiveness to different sources of LPS is equivalent to or varies with the source of LPS. Therefore, in this report, we examined the extent of the human monocyte response to LPS derived from two oral pathogens, Actinobacillus actinomycetemcomitans (Aa) and Porphyromonas gingivalis (Pg). Additionally, due to its well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
109
1
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(121 citation statements)
references
References 23 publications
8
109
1
3
Order By: Relevance
“…Initially, the immunomodulating capacity of LAB was only referred to the induction of antibody production or the cellular response. Actually, considering the important role played by biological messengers as cytokines in the balance of the immune response, a lot of research work has been done to demonstrate the influence of LAB in the cytokine release signalling pathways for the production of cytokines (Agarwal et al, 1995;Miettinen et al, 1996Miettinen et al, , 2000Maassen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the immunomodulating capacity of LAB was only referred to the induction of antibody production or the cellular response. Actually, considering the important role played by biological messengers as cytokines in the balance of the immune response, a lot of research work has been done to demonstrate the influence of LAB in the cytokine release signalling pathways for the production of cytokines (Agarwal et al, 1995;Miettinen et al, 1996Miettinen et al, , 2000Maassen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the neutrophil has been shown to have the ability to produce a number of immunomodulators, cytokines in particular, that may regulate the inflammatory cascade [3][4][5][6]. Among those, IL-8, TNF-and IL-1 have particular importance [3,[7][8][9][19][20][21]. At sites of inflammation, as well as in the systemic circulation, leucocytes elaborate cytokines in response to various proinflammatory agonists.…”
Section: Discussionmentioning
confidence: 99%
“…IL-8, TNF-and IL-1 have been shown to strongly influence neutrophil function in a variety of experimental and clinical settings [3,[7][8][9]. Further, PMN function is regulated by its interactions with extracellular matrix through integrin molecules [2,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that the numbers of this micro-organism are increased in patients with periodontal disease, especially those with early-onset periodontitis [3][4][5][6]. Human monocytes and polymorphonuclear neutrophils stimulated with this potential periodontopathogen have been shown to release proinflammatory cytokines, such as interleukin (IL)-1, IL-6, IL-8 and tumour necrosis factor (TNF-AE) [7,8]. A. actinomycetemcomitans has been shown to induce alveolar bone destruction in animal models [9].…”
Section: Introductionmentioning
confidence: 99%